Philosophical logic - Strawson, P. F. (Oxford Oxford university press, 1967)
Although the ordinary-language branch of analytic philosophy began as an effort to dissolve philosophy, Peter F. Strawson, who has been one of its major voices, has shown that this approach can be enlarged to address many of the great themes of the Western tradition. Strawson was born in England and educated at Oxford University. After military service during World War II and a brief period of teaching in Wales, he returned to Oxford, where he has remained. Strawson's Introduction to Logical Theory (1952) shows that symbolic logic does not capture the complexity of ordinary language. He therefore argues for a logic of everyday discourse that can capture the conditions under which we use logical construction to express ourselves. He tries to show that some classes of valid arguments are not recognized as such within formal systems and that Aristotelian logic can be defended as preferable to modern logic. Strawson's emphasis on language continues in his later work, in which he uses linguistic structures to address metaphysics and epistemology. His book on Immanuel Kant, for example, uses language to rework a priori knowledge. Individuals (1959) begins his work in descriptive metaphysics by proposing that the concept of the person be taken as philosophically primitive. This, he believes, would avoid two equally incoherent views, the first being Cartesian dualism, the second being the view that states of consciousness can be discussed without reference to a knowing subject.